IMPORT SUBSTITUTION IN RUSSIA AS DEVELOPMENT FACTOR IN GLOBAL CHALLENGES PERIOD OF 2017–2019 - N. I. Komkov; N. N. Bondareva (Модернизация, инновация, развитие)
Purpose: objectives of research: 1) Justification of a new role of import-substituting strategy as factor of large-scale import-substituting industrial revolution in the Russian Federation, an economic development driving force; 2) Confirmation of expediency of complex synergetic innovative tools of state support on decrease in import technology dependence of the Russian Federation, increase in dynamics of industry growth, technological potential and export of technologies; 3) The proof of progressiveness of scaling of import substitution as new key strategy of Russia development taking into account the best international experience, public and private initiatives and risks of import substitution.Methods: the methodology of the work is based on a modeling of scenarios, analysis of open statistical sources, projections and calculations, forecasting methods.Results: on the basis of the analysis of statistics a positive assessment is given to methodologically progressive instruments and mechanisms of realization of strategy of import substitution in the Russian Federation with the proved or potential efficiency taking into account national specifics. New national advantages and benefits of overcoming the degrading consumer market in Russia in 2014–2015 are shown. Processes of transformation and creation of the new national market on the basis of import substitution are described. The forecast of achievement of planned targets for import substitution programs in the Russian Federation on condition of further total economy modernization for import substitution is developed.conclusions and relevance: the statistics of large-scale revolutionary transition of the enterprises of the Russian Federation to a full cycle of production instead of the short technological chains which have taken roots in the last 20 years is collected. The problems and risks which are slowing down progress in import substitution in the Russian Federation are revealed. The role of RAS as chief scientific expert of the Russian Federation in realization of policy of import substitution is noted. The methodology of state support from the Industry Development Fund and Rostec is estimated. Strong advantages of a regional component of the state program approach in import substitution are revealed. Methods of strengthening of regional industrial competences and their global marketing as state support instruments are revealed.